Do papel dos atos ilocucionários na teoria da pragmática formal do discurso de Daniel Vanderveken - Barbosa, Igor Gabriel de Almeida (2025)
The present dissertation work has the general objective of analyzing and clarifying the role of the theory of speech acts – specifically, the speech acts of the illocutionary type – in the development of the theory of formal pragmatics of discourse (the theory of conversations) elaborated by Daniel Vanderveken. To this end, it is necessary to present the theory of illocutionary acts and explain why, due to its limitations, it is not sufficient to explain the logical structure of conversations or entire discourses. The speech acts theory is limited to the analysis of first-level illocutionary acts, that is, isolated, individual and momentary illocutions that agents (speakers and hearers) perform when using elementary statements, in contexts of language use. This theory does not analyze the logical structure of entire discourses that protagonists conduct during a conversation. Thus, our work has the following objectives: to present the state of the art of the problem or theme in order to show the historical-theoretical path of the speech acts theory standard, from Austin and Grice to Searle and Vanderveken, mentioning some observations and notions added by Vanderveken and Sousa Melo; to elucidate skeptical position of Searle who, in the wake of the second Wittgenstein, does not believe it is possible to develop a theory of entire discourses as rigorous as the theory of first-level illocutionary acts; to discuss Searle's arguments against the possibility of conceiving such a theory and explain how Vanderveken responds to this challenge; to present the theory of formal pragmatics of discourses elaborated by Vanderveken, where he presents the general logical principles and a typology of entire discourses or conversations whose objective is purely discursive; finally, to talk about Searle's change of position after Vanderveken developed his theory and therefore superimpose his challenge.